Hydromechanical Modeling of Fault Rupture in Geologic CO2 Sequestration: A Comparison of Two Failure Criteria - M. Cao; Y. Guglielmi; J. Rutqvist; A. Cihan; S. Glubokovskikh; P. Jordan; M. Reagan; J. Birkholzer (Geophysical Research Letters)
Abstract The large‐scale implementation of geological carbon sequestration has raised concerns about potential fault activation and induced seismicity, which could compromise storage integrity and pose seismic risks. We theoretically compared two failure criteria, Mohr‐Coulomb (MC) and Modified Cam‐Clay criteria (MCC), to assess fault rupture during CO2 storage. Both criteria characterize fault behavior in a specific stress regime but differ in reducing the complexity of fault rupture to a few key mechanisms. Using a coupled hydromechanical model, we demonstrate that the choice of a failure criterion and the physics of fault weakening associated with these criteria strongly condition fault response to a given fluid injection. MC mainly relates rupture to friction, while MCC relates rupture to fault poro‐plasticity. Our findings highlight that the selection of a failure criterion, being inherently subjective, can significantly alter the predicted fault behavior during CO2 storage, thereby impacting the reliability of geomechanical risk assessments.